Effect of black soldier fly larva meal on broiler chicken production, meat quality, and it"s physiological properties: a meta-analysis - Shekhar CHHETRI; Faisal FIKRI; Agus PURNOMO; Hakan ÇALIŞKAN; Muhammad Thohawi Elziyad PURNAMA (Kafkas Universitesi Veteriner Fakültesi Dergisi)
This study assessed the effect of feeding black soldier fly larva (BSFL) on broiler chicken production, meat quality, and physiological characteristics using a meta-analysis. Out of the 1878 articles that were reviewed from five databases (PubMed, Scopus, Science Direct, Cochrane Library, and ProQuest), 21 papers were selected for meta-analysis using the specific keywords "black soldier fly, Hermetia illucens, broiler chickens, growth performance" and the PRISMA flow diagram. The R Studio software version 4.4.2 (Posit PBC, USA) was employed to analyze the meta-analysis and compute the standard mean difference (SMD), 95% confidence interval (CI), and random effects. The current meta-analysis demonstrated that providing BSFL meals for broiler chickens had a favorable impact on weight gain, feed efficiency, carcass percentage, breast and thigh muscles, cooking loss, drip loss, meat color lightness, and yellowness. On the other hand, favorable effects were also reported on erythrocytes, packed cell volume, mean corpuscular volume, heterophil: lymphocyte (H/L) ratio, serum glucose, alanine transaminase, aspartate aminotransferase, gamma-glutamyl transferase, blood urea nitrogen, creatinine, uric acid, calcium, phosphorus, magnesium, and iron. It has been demonstrated using a meta-analysis study that the BSFL meal is beneficial for weight gain, feed efficiency, meat quality, and physiological properties in broiler chickens.